Treatment strategies in osteoporosis - an analysis of practice guidelines - Pelin, Ana-Maria; Georgescu, Costinela; Stefan, Simona Claudia; Dragostin, Oana; Balan, Gabriela (Progress in Nutrition, 2021)
The goal of this paper is to present the sequential therapies used in the treatment of osteoporosis, according to the new practice guidelines.Various specialized e-platforms have been searched (PubMed, Scopus, Web of Science), as well as forums specializing in the treatment of osteoporosis, American Association of Clinical Endocrinologists (AACE/ACE), National Osteoporosis Foundation (NOF) ACR (American College of Rheumatology) and ISCD (International Society for Clinical Densitometry) and the new osteoporosis treatment guidelines have been analysed.The therapeutic agents used in the treatment of osteoporosis have antiresorptive action or osteoforming action. The studies performed until the present did not show the superiority of associating the two types of medication as compared to each of them considered separately. When bisphosphonates are contraindicated, there is intolerance or the obtained results are minimum, human, anti-RANKL (denosumab) monoclonal antibodies may be administered, which inactivate the osteoclasts and their development. The hormone replacement therapy, as well as the selective estrogen receptor modulators (raloxifene), has very limited indications due to the severe adverse reactions (thromboembolism, endometrium cancer, breast cancer, cardiovascular diseases). At present, numerous preparations having antiresorptive action or osteoforming action are being studied: sclerostin inhibitors (romosozumab), Cathepsin K inhibitors (odanacatib), integrin inhibitors (proteins involved in osteoclasts’ adhesion), new parathormone derivates. The new administration methods of the existing preparations are equally possible future approaches of the osteoporosis treatment.